Investigating the Effect of Drugs of Chloramphenicol and Gentamicin on Acanthamoeba genotype T3 Causing keratitis Isolated from Environmental samples in vitro (Baghdad Science Journal, 2022)
This study is an investigation of the drugs effect on some pathogenic Acanthamoeba isolated from Iraqi waters, where the problem of environmental adaptation that characterizes this organism in addition to being a reservoir for many pathogenic microorganisms that take shelter in it to escape disinfectants and medicines is sometimes difficult to treat it with traditional treatments.  Twenty water samples were collected from different water regions in Iraq, namely the Dokan Lake, Tigris River, Euphrates River and Najaf Sea, 5 samples from each source.  Acanthamoeba was isolated from water samples on NNA and PYG media, using an inverted microscope with an electron microscope to determine their phenotypic features. PCR and Sequencing were also used to determine their genotype. The isolates were belonged to the T3 genotype that causes corneal infections. Then two types of drugs were used to treat it, which were Chloramphenicol and Gentamicin at three different concentrations, 0.1%, 0.3% and 0.6% and their inhibitory effect was compared with each other and with the positive control of the Chlorohexidine drug at a concentration of 0.2% which was recommended to treat Acanthamoeba keratitis. The results showed that both drugs have an inhibitory effect against Acanthamoeba growth, and that the chloramphenicol had more effect to inhibit compared with gentamicin and chlorhexidine, and it can be used as an alternative treatment instead of chlorohexidine for treating Acanthamoeba keratitis.